Marketing Planning in Housing Construction - Chychkalo-Kondratska, Iryna; Dobryanska, Viktoriia; Miroshnichenko, Volodymyr (International Journal of Engineering and Technology, 2018)
The construction company marketing planning process considering market possibilities under optimum using of the available resources is being investigated in the article. Usage of the General Electric corporate method at the marketing strategic planning level is considered. The improvement of General Electric approach with the help of the factors importance calculating by hierarchy method which makes strategic assessment more precise is suggested in the article. The list and hierarchy of factors have been received based on two-stage expert enquiry by L.S. Shkolnik Â«erectorÂ» method. At the level of tactical planning the method of linear programming is applied to optimize the use of resources. The offered methods enable making strategic business estimation more exact, and to spend resources of the organization with maximum efficiency at strategic plans implementation .Â